Screen Space Reconfigured - Saether, Susanne; Bull, Synne Tollerud (MediaMatters, 2020)
Screen Space Reconfigured is the first edited volume that critically and theoretically examines the many novel renderings of space brought to us by 21st century screens. Exploring key cases such as post-perspectival space, 3D, vertical framing, haptics, and layering, this volume takes stock of emerging forms of screen space and spatialities as they move from the margins to the centre of contemporary media practice.Recent years have seen a marked scholarly interest in spatial dimensions and conceptions of moving image culture, with some theorists claiming that a 'spatial turn' has taken place in media studies and screen practices alike. Yet this is the first book-length study dedicated to on-screen spatiality as such.Spanning mainstream cinema, experimental film, video art, mobile screens, and stadium entertainment, the volume includes contributions from such acclaimed authors as Giuliana Bruno and Tom Gunning as well as a younger generation of scholars.